Spalling behaviours of railway wheel under cyclic loading - Ong, Ting Wei (2019)
This project aims to investigate spalling behaviours of railway wheel under cyclic loading. Spalling are voids or edge cracks which form and grow due to rolling contact. Typically, cyclic loading will result in fatigue cracks to grow at the white etching layer of the wheel. Pre-existing cracks on wheels would grow due to cyclic loading until it causes the wheels to fail. Failures of railway wheels can result in disastrous train accidents, hence design against failure is important. This study analyse the parameters which will affect the number of cycles taken for cracks to grow to an unacceptable length. In this project, ABAQUS Version 6.14 would be used to perform Extended Finite Element Method (XFEM) for different test simulations. The focus of the project would be to analyse the relationship between different initial crack angles and crack propagation rates. In addition, further studies would be done to analyse the effects of increasing numbers of pre-existing cracks, increasing loads, and varying material properties.